Akumulasi dan Prediksi Tingkat Penjualan Minuman dengan Menerapkan Metode Monte Carlo - Syaputra, Aldo Eko; Eirlangga, Yofhanda Septi (Jurnal Informasi dan Teknologi, 2022)
25 Coffee has increased sales every day. This situation causes service to consumers to be disrupted because raw materials often run out. Some consumers do not get good service and some even wait too long but do not get the desired item. This situation will cause consumers to be reduced because they move to another seller's place. So this research is carried out to predict sales in maintaining the availability of raw materials so that services are guaranteed and improved. The method used in this study is Monte Carlo by processing sales data in 2019, 2020, and 2021. The results of this study are able to predict the number of beverage sales in the following years with an average accuracy rate of 91%, in 2020 , and 89% in 2021. So this prediction becomes a reference material for 25 COFFE parties to make decisions and improve services.